US and Japan rivalry in Philippine interwar import manufactures market: Power politics, trade cost and competitiveness - Alejandro Ayuso-Díaz; Antonio Tena Junguito (European Historical Economics Society (EHES), 2024)
This paper investigates the impact of hurricanes on school attendance in Jamaica from 1892 to 1942, a period marked by significant natural disasters, including four category two hurricanes. By integrating monthly school attendance data from the fourteen Jamaican parishes with assessments of potential storm destruction, the paper quantifies the effect of hurricanes on school attendance. The average effect of a category two hurricane was a 9.1% decrease in school attendance in the month of the hurricane, followed by decreases of 8.6% and 7.2% in the following two months. Consequently, nearly 400 children miss school for one month, with over 310 children missing school for three months. Mediation analysis further indicates a decline in school performance by up to 3.23%, indirectly caused by decreased school attendance. This paper highlights the lasting impact of hurricanes on educational outcomes, especially in countries with agrarian economies and underdeveloped education systems.This study examines the asymmetric protectionist policies of the U.S. in the Philippine market during the interwar period, focusing on how these policies effectively marginalized European powers and the emerging Japan before the Yen devaluation in 1931. Using a new database on product and country-level imports from 1913 to 1940, the study concludes that competition was most intense in cotton textiles between the U.S. and Japan. The literature identifies a devalued Yen, lower transport costs, and cheaper prices of cotton manufactures as key Japanese advantages that counterbalanced U.S. protectionism in the Philippines. Regression analysis indicates that tariffs hindered cotton textile exports to the Philippines during the interwar years, especially affecting Japanese exports before the Great Depression. Japanese competitiveness before the 1930s relied on government-supported lower freight rates. However, after the Yen devaluation in 1931, the effectiveness of tariffs diminished, and the devaluation became the principal driver of Japanese textile exports to the Philippines. To counter this advantage, the USA and Japan agreed to an export restraint in exchange for tariff stabilization at the start of the Commonwealth period in 1935. However, this agreement failed to reduce the value of Japanese cotton textile exports to the Philippines. A significant reduction occurred only after the outbreak of the Sino-Japanese War in 1937.
Keywords: F13; F15; N75; 330; Asymmetric tariff policy; US colonial markets; commercial power politics; trade cost; exchange rate policy; competition in colonial markets; import margins